FUNCTIONAL STATUS OF HEART AND KIDNEYS AND CARDIO-RENAL INTERACTIONS IN PATIENTS AFTER CORONARY REVASCULARISATION INTERVENTION - M. E. Statsenko; D. V. Bolotov (Российский кардиологический журнал)
Aim. To assess cardio-renal interactions and the functional status of heart and kidneys in patients with acute myocardial infarction (AMI) who underwent the post-AMI coronary revascularisation. Material and methods. In total, 100 men, aged 45–60 years, were examined, including 50 AMI patients who underwent the revascularisation surgery. Cardiac structure and function, as well as excretory, glomerular, and tubular renal functions, were assessed. Results. Patients who underwent revascularisation demonstrated lower creatinine levels. In this group, the prevalence of the serum creatinine concentration >115 μmol/l and glomerular filtration rate (GFR) < 60 ml/min was significantly lower than in the patients treated conservatively. Urine levels of β2-microglobulin, reflecting the tubular renal function, were significantly lower in AMI patients after revascularisation. In addition, the revascularisation group demonstrated an improvement in cardio-renal interactions, compared to the conservative treatment group. Conclusion. Among AMI patients who underwent coronary revascularisation, in comparison to the patients treated conservatively, there was an improvement in cardio-renal interactions and a positive dynamics in both cardiac structure and function and renal functional status. In the revascularisation group, renal function parameters were significantly associated with the parameters of cardiac structure and function, which confirmed the existence of cardio-renal interactions.